Facing the Indonesian Media Conglomeration: Action of Preservation on Political Interest (Jurnal Kajian Media, 2017)
After 1999, Indonesia's Media became grown up. It is the implication of the fallen of the authoritarian regime, Suharto. The growth has another side effect about trends of media conglomeration. Indonesian Media Conglomerate such as Tanoesoedibjo, Tandjung, Paloh and Bakrie also have the background as a politician. Mass media are an efficient tool to change the mind of people. Mass society theory makes several basic assumptions about individuals, the role of media, and the nature of social change. Media owner used their media for preserving his political influences. Facing this situation, Indonesian regulation about media ownership ignored by media owners. They used their power in the political area to get away from the regulation. Whereas, in Indonesian Law Number 32, issued on 2002 about Broadcasting Media, Especially on Chapter 36 verse 4 states, "broadcast content must be maintained neutrality and should not put the interests of a group". Many complain from the media audience, but no action from the government. The regulator doesn't enforce the law, especially at Broadcast Media. Most of the press uses the public sphere, who design for democratisation process, not for individual or political party's interest. Keywords: media conglomeration, Indonesia, Politics